Investigator triangulation in the data interpretation process. An almost untouched research area - Schippling, A. (La Critica Sociologica, 2017)
In actual discussions and especially in the context of improving the quality of qualitative research, investigator-triangulation is understood as one strategy to obtain a more complex and profound understanding of the research object. Although investigator-triangulation is mentioned in methodological debates, there is very little scienti c re ection and research about its practice and implications for the research process, especially for data analysis. Everyday practice of interpretation groups composed of social sciences researchers, who interpret qualitative data, is still an almost untouched research area. This contribution proposes a methodological re ection on investigator triangulation in in- terpretation groups in social sciences, inspired by the empirical experience of group inter- pretation of data gathered for an ongoing research project about international schools in Greater Lisbon in the context of a German research workshop. Based on a concrete example of joint interpreting interviews, we will not only discuss the methodological implications, challenges and potentials of investigator triangulation and the generation of knowledge with- in interpretation groups, but also shed a light on research perspectives within this context.